Regulatory Mechanisms of Mitochondrial Autophagy: Lessons From Yeast - Furukawa, Kentaro; Innokentev, Aleksei; Kanki, Tomotake (Frontiers in Plant Science, 2019)
Mitochondria produce the majority of ATP required by cells via oxidative phosphorylation. Therefore, regulation of mitochondrial quality and quantity is important for maintaining cellular activities. Mitophagy, the selective degradation of mitochondria, is thought to contribute to control of mitochondrial quality and quantity. In recent years, the molecular mechanism of mitophagy has been extensively studied in yeast and mammalian cells. In particular, identification of the mitophagy receptor Atg32 has contributed to substantial progress in understanding of mitophagy in yeast. This review summarizes the molecular mechanism of mitophagy in yeast and compares it to the mechanism of mitophagy in mammals. We also discuss the current understanding of mitophagy in plants.